2015
DOI: 10.1371/journal.pone.0119564
|View full text |Cite
|
Sign up to set email alerts
|

Eugenol: A Phyto-Compound Effective against Methicillin-Resistant and Methicillin-Sensitive Staphylococcus aureus Clinical Strain Biofilms

Abstract: BackgroundInhibition and eradication of Staphylococcus aureus biofilms with conventional antibiotic is difficult, and the treatment is further complicated by the rise of antibiotic resistance among staphylococci. Consequently, there is a need for novel antimicrobials that can treat biofilm-related infections and decrease antibiotics burden. Natural compounds such as eugenol with anti-microbial properties are attractive agents that could reduce the use of conventional antibiotics. In this study we evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
135
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(162 citation statements)
references
References 51 publications
9
135
0
1
Order By: Relevance
“…This is in line with Kyaw and Lim (2012) which reported that eugenol which is a bacteriostatic phytochemical (Rastogi et al, 2008;Yadav et al, 2015) in combination with a bacteriostatic antibiotic minocycline produced indifference interaction. According to Qin et al (2013), indifference is when the combined action is the same as with either component alone.…”
Section: Discussionsupporting
confidence: 84%
“…This is in line with Kyaw and Lim (2012) which reported that eugenol which is a bacteriostatic phytochemical (Rastogi et al, 2008;Yadav et al, 2015) in combination with a bacteriostatic antibiotic minocycline produced indifference interaction. According to Qin et al (2013), indifference is when the combined action is the same as with either component alone.…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, it is envisaged that eugenol is effective against ica-independent biofilm formation. Similar findings were reported with eugenol in inhibition of biofilms of MRSA strains of clinical origin [14,38].…”
Section: Effect Of Eugenol On B-galactosidase Activitysupporting
confidence: 88%
“…It is also important industrially and has been used as a flavouring agent in food and cosmetic products [13]. Recently, biofilm inhibition and eradication properties of eugenol against MRSA and methicillin-sensitive S. aureus (MSSA) clinical strains have been reported [14]. However, the effect of eugenol on QS and biofilm of MRSA strains isolated from food handler's is not studied yet.…”
Section: Introductionmentioning
confidence: 99%
“…At sub-MIC eugenol significantly decreased 88% S. aureus colonization in rat middle ear. MBEC (minimum biofilm eliminating concentration) of eugenol and carvacrol combination decreased the already formed biofilms by 99% [30]. Eugenol at 0.5 MIC was able to induce an inhibition of ≥ 90% of P. aeruginosa biofilms [31].…”
Section: Antioxidant Activity Of Eugenolmentioning
confidence: 99%